Relationship between School Culture and Work Motivation in Vocational High Schools - Putri Anandita; Anisah Anisah (Universitas Negeri Padang, 2021)
The research is based on the results of the author's observations showing that the teacher's motivation is not optimal. Therefore, many factors affect work motivation, one of which is organizational culture. The purpose of the study was to determine: 1) work motivation, 2) school culture and 3) the relationship between organizational culture and work motivation. The hypothesis of the research is